(untitled) (Revista de História da UEG (REVHIST), 2020)
Abstract: This article proposes an investigation of the legal status of free Africans and their going to Itaboraí, within a context of measures to repress trafficking and its repercussions on Brazilian slave society. The analysis verifies the sending of these Africans out of the Court because of the political relations in favor of certain groups, as well as the result of actions of the Imperial State, in the aim of achieving progress in the Province of Rio de Janeiro. Through these investigations, this study seeks to demonstrate how this County, especially the region of the Village of São João de Itaboraí, was inserted in the initiatives and political relations developed in the Imperial Court. Keywords: Illegal traffic. Free Africans. Itaboraí.